Does earmarked donor funding make it more or less likely that developing countries will allocate their resources towards programmes that yield the greatest health benefits? - Catriona Waddington
It should not be assumed that earmarked donor funding automatically increases the allocation of developing-country resources towards programmes that yield the greatest health benefits. Sometimes it does, sometimes it does not - how the funding is designed can influence this. This is true particularly in the longer term, once the earmarked funding has ended. Even in the short term, total funding does not necessarily increase because of fungibility (i.e. recipient governments adjust their spending to offset donor funding preferences). The author explores six problems with earmarked funding: the multiplicity of earmarked funds confuses the situation for decision-makers; earmarking works against the spirit of the sectorwide approach; from the national perspective, it makes sense not to double-fund activities; local ownership of an activity is often compromised; earmarking can lead governments to accept interventions which they cannot afford in the longer term; and earmarking can distort local resource allocation.